Решите выражение : 1) (3x-8y)^2+6x(9x+8y) 2) (-7x+2y)^2-14x(3x-2y)

Jisbihish Jisbihish    3   31.07.2019 00:00    0

Ответы
rkbsiti rkbsiti  03.10.2020 18:05
(3x-8y)² +6x(9x+8y) =
= 9x² -2*3x*8y +64y² +54x² +48xy=
= (9x²+54x²) +64y² -48xy  + 48xy=
= 63x²+64y²

(-7x +2y)²  - 14x (3x-2y) =
= (-7x)² + 2*(-7x)*2y +4y² - 42x² +28xy=
= 49x² - 28xy +4y² -42x²+28xy=
= 7x² +4y²
ПОКАЗАТЬ ОТВЕТЫ
Не123098 Не123098  03.10.2020 18:05
1)...=9x²-48xy+64y²+54x²+48xy=63x²+64y².
2)...=(2y-7x)²-42x²+28xy=4y²-28xy+49x²-42x²+28xy=4y²+7x².
ПОКАЗАТЬ ОТВЕТЫ
Другие вопросы по теме Алгебра